2014
DOI: 10.1111/jog.12540
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prolonged dinoprostone cervical ripening on the rate of artificial induction of labor: A prospective study of 330 patients

Abstract: This study allows us to show for the first time that sustained-release of dinoprostone leads to spontaneous induction of labor without increasing the obstetrical risk in a majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…There are many studies looking at IOL in women with one previous CS, but they collect all methods of induction as one group (PG, cervical catheter, and augmentation with ARMs). [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies looking at IOL in women with one previous CS, but they collect all methods of induction as one group (PG, cervical catheter, and augmentation with ARMs). [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absence of adequate data about the related risks, such as length of hospitalization, postpartum hemorrhage and hyperstimulation, leads to an observation that analysis of safety was greatly contracted. Although a study reported that sustainedrelease of dinoprostone led to spontaneous induction of labor without increasing the obstetrical risks in a majority of patients (45) but further investigation about this issue should be conducted in the future.…”
Section: Description Of Populations and Methods Of Randomization Ofmentioning
confidence: 99%